Entre comunicação e educação: narrativas audiovisuais de professores de Uberlândia-MG sobre o ensino de História na Educação de Jovens e Adultos - Ramos, Aline Alves (2020)
This research proposed to understand how History teaching professionals who work in Youth and Adult Education (EJA) classes in the municipal schools of Uberlândia-MG build the History teaching process with young and adult students, and what is the meaning of this discipline for their citizen formation. Inserted in the field of Oral History, we recorded six teaching narratives - three teachers who work in the early years (1st to 5th year) and three teachers who work in the final years (6th to 9th year) - about knowledge and educational practices related to the teaching of History at EJA and the meaning they seek to give to their professional performance. From this, two audiovisual products were elaborated: the videos of each interview in full and a thematic documentary crossing different narratives, both made publicly available on the digital platform “Observatory of Teaching History and Geography” (https://observatoriogeohistoria.net.br/). The objective of these products was to promote the social visibility of the teaching action in the process of teaching History in Basic Education, in the peculiarity of Youth and Adult Education, to broaden the view on this modality and contribute to the understanding of its specificity and, still, collaborate for the valorization of knowledge and skills, which are fundamental for the structuring of the teaching profession. Thus, in the midst of a set of knowledge (curricular, didactic, experience) we discover that the knowledge of experience or practice has a fundamental importance in defining the professional identity of the EJA teacher. As these narratives will remain on the platform indefinitely, they will be preserved as sources for further research on the topic, allowing for later readings and interpretations, in addition to our own that aimed to produce audiovisuals, crossing different experiences and views on different dimensions of the subject in question. Finally, we emphasize that the documentary produced reflects the way we present the results of the research, that is, it is the result of the research movement that we did; it is our analysis of the teaching narratives, our look at them.